Clinical Features and Outcomes in Pediatric Autoimmune Encephalitis Associated With CASPR2 Antibody - Tan, Chengbing; Jiang, Yan; Zhong, Min; Hu, Yue; Hong, Siqi; Li, Xiujuan; Jiang, Li (Frontiers in Pediatrics, 2021)
Background: Contactin-associated protein-like 2 (CASPR2) neurological autoimmunity has been associated with various clinical syndromes involving central and peripheral nervous system. CASPR2 antibody-associated autoimmune encephalitis is mostly reported in adults. Analysis of the clinical presentation and prognostic data of CASPR2 antibody-associated autoimmune encephalitis in children remains important. Methods: A single-center retrospective review of children diagnosed with CASPR2 antibody-associated autoimmune encephalitis from June 1st, 2018 to October 31st, 2020. Results: Six patients were identified. The median age was 12 years(range 1.8-14), with an overall male predominance of 83% (5/6). Commonest clinical features were psychiatric symptoms (6/6), movement disorders (4/6), altered consciousness (3/6), sleep disorders (3/6) and headache (3/6). Four patients (4/6) received first-line therapy alone (steroids combined with intravenous immunoglobulins), and two patients (2/6) received second-line therapy (rituximab, mycophenolate mofetil or cyclophosphamide). All patients showed no peripheral nervous system involvement. One patient had comorbidities with systemic lupus erythematosus. No evidence of neoplastic disease was found in the whole cohort. All patients had favorable outcomes (modified Rankin Score 0–2) with recurrence rate at 0%, respectively. Conclusion: CASPR2 antibody-associated autoimmune encephalitis is rare in children. Our findings suggest that this type of encephalitis seems to occur more frequently in older children. Patients respond well to immunotherapy and usually demonstrate a favorable clinical outcome. Associated tumors are extremely rare.